THE PHENOMENON OF MISSIONARY ACTIVITY OF CHRISTIAN CHURCHES IN THE VIRTUAL SPACE - Lomachinska, Irina; Grebenyuk, Petro (Skhid, 2020)
The challenges of the modern globalizing information society are forcing the Christian confessions to give a new meaning to the value orientations of missionary activity and to improve its forms and means. Thanks to the active development of the Internet, the Christian confessions receive new opportunities not only for the implementation of missionary practices aimed at deepening spiritual values among the believers of their religious communities, but also advantages in the dissemination of religious ideas, values, beliefs among non-Christians, therefore, the purpose of the article is to determine the features of the forms and directions of evangelistic missionary practices of the Catholic and Orthodox Churches in the virtual space. The research methodology is based on the principles of non-confessionalism and worldview pluralism, with the involvement of systemic, comparative methods, analysis and synthesis. The conclusions emphasize that the problem of using network technologies for missionary activity is in constant dynamics, forcing the Catholic and Orthodox churches to actively respond not only to changes in value public orientations, but also to the active dissemination of technical innovations. The modern Christian Internet resources are focused mainly on the information function, however, the effectiveness of the missionary practices is ensured by the dominance of the communicative function. The modern Catholic missionary activity is focused on the idea of enculturation as the meeting of the Christian message with the non-Christian community in its cultural context. The Orthodox missionary activity is aimed at preserving and disseminating traditional national religious and cultural values of the Orthodox communities.